2021
DOI: 10.1111/epi.16978
|View full text |Cite
|
Sign up to set email alerts
|

Early‐life epilepsy after acute symptomatic neonatal seizures: A prospective multicenter study

Abstract: Objective We aimed to evaluate early‐life epilepsy incidence, seizure types, severity, risk factors, and treatments among survivors of acute neonatal seizures. Methods Neonates with acute symptomatic seizures born 7/2015‐3/2018 were prospectively enrolled at nine Neonatal Seizure Registry sites. One‐hour EEG was recorded at age three months. Post‐neonatal epilepsy and functional development (Warner Initial Developmental Evaluation of Adaptive and Functional Skills – WIDEA‐FS) were assessed. Cox regression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
2
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 45 publications
1
18
2
1
Order By: Relevance
“…One of the concerns of unnecessary continuation of ASMs is that preclinical models have demonstrated neuronal apoptosis and disruption of synaptic development when mammals are exposed to ASMs. 2,3 The data presented in this study 1 do not appear support the preclinical data regarding functional neurodevelopment.…”
Section: Safety Of Early Discontinuation Of Antiseizure Medication Af...contrasting
confidence: 68%
See 1 more Smart Citation
“…One of the concerns of unnecessary continuation of ASMs is that preclinical models have demonstrated neuronal apoptosis and disruption of synaptic development when mammals are exposed to ASMs. 2,3 The data presented in this study 1 do not appear support the preclinical data regarding functional neurodevelopment.…”
Section: Safety Of Early Discontinuation Of Antiseizure Medication Af...contrasting
confidence: 68%
“…We found no added benefit for centralized review to estimate risk of infantile spasms and other epilepsies. 3,4 Further, if centralized review adds rigor, we would not alter our recommendations to discontinue ASM, since the medications currently used to treat acute neonatal seizures do not prevent epilepsy (and are not appropriate to treat infantile spasms).…”
Section: Safety Of Early Discontinuation Of Antiseizure Medication Af...mentioning
confidence: 99%
“…5 The findings from the study by Shelhaas et al suggest that severity of acute symptomatic seizures and its successful control is a predictor of developing later epilepsy. 6 Wietstock et al had found that in neonates with seizures, initial neurocritical care (hypothermia programme, continuous EEG monitoring, seizure management guidelines and ongoing staff education) is important in determining the dose of ASM and the duration of maintenance ASM therapy. 7 Incorporating these factors in future studies could provide information on safety of discontinuing ASM, and its relation to risk of postneonatal seizure disorders.…”
Section: Commentarymentioning
confidence: 99%
“…Additionally, among neonates with HIE, seizures have been associated with an increased risk for subsequent neurobehavioral problems and epilepsy. 2,[4][5][6][7] Due to the high risk of seizures in this population, guidelines recommend that neonates with HIE undergo continuous EEG monitoring (CEEG) liberally during the therapeutic hypothermia and return to normothermia periods, which often last 4-5 days. 8,9 However, this practice is resource-intensive and not feasible for all neonates who might benefit, 10 as many neonates receive care in neonatal intensive care units without CEEG capability and approaches to remote CEEG are new and not yet widely available.…”
Section: Introductionmentioning
confidence: 99%